A Highly Sensitive Low-Temperature N-Butanol Gas Sensor Based on a Co-Doped MOF-ZnO Nanomaterial Under UV Excitation - Yinzhong Liu; Xiaoshun Wei; Yun Guo; Lingchao Wang; Hui Guo; Qingjie Wang; Yiyu Qiao; Xiaotao Zhu; Xuechun Yang; Lingli Cheng; Zheng Jiao (Sensors)
Volatile organic compounds (VOCs) are presently posing a rather considerable threat to both human health and environmental sustainability. Among these, n-butanol is commonly identified as bringing potential hazards to environmental integrity and individual health. This study presents the creation of a highly sensitive n-butanol gas sensor utilizing cobalt-doped zinc oxide (ZnO) derived from a metal–organic framework (MOF). A series of x-Co/MOF-ZnO (x = 1, 3, 5, 7 wt%) nanomaterials with varying Co ratios were generated using the homogeneous co-precipitation method and assessed for their gas-sensing performances under a low operating temperature (191 °C) and UV excitation (220 mW/cm2). These findings demonstrated that the 5-Co/MOF-ZnO sensor presented the highest oxygen vacancy (Ov) concentration and the largest specific surface area (SSA), representing the optimal reactivity, selectivity, and durability for n-butanol detection. Regarding the sensor’s response to 100 ppm n-butanol under UV excitation, it achieved a value of 1259.06, 9.80 times greater than that of pure MOF-ZnO (128.56) and 2.07 times higher than that in darkness (608.38). Additionally, under UV illumination, the sensor achieved a rapid response time (11 s) and recovery rate (23 s). As a strategy to transform the functionality of ZnO-based sensors for n-butanol gas detection, this study also investigated potential possible redox reactions occurring during the detection process.